Pengelolaan Keuangan Publik Islam Perspektif Historis - Noviyanti, Ririn (Iqtishodia: Jurnal Ekonomi Syariah, 2016)
The instrument of public finance include of zakat, wakaf and infaq. Optimal management of public finance will be able to reach the purpose of human life welfare. The aim of this research is to describe the management of public finance in the classical Islamic period. Specifically at Rasulullah, Shahabah, Umayyah, Abbasiyah and Ustmani period. This reseach uses descriptive - qualitative method with socio ??? historical approach, which will study about the events of the past on public financial management and to describe the human lives of that period.The conclution of this study, that there are two things that become the foundation of public finance management in classical Islamic period (1). Prioritizes of maslahah (2). Implementing the simplicity life style (qana'ah).